(untitled) (Revista de Investigaciones Universidad del Quindío, 2011)
This article is about the functioning of social activities that are offered to people over 60 years old residing in urban settings and living in poverty or in extreme poverty. This project presents some of the results of another project named in the same way and financed by the research department of the University of Quindío. The study sample was composed of 591 people over the age of 60 who were classified in levels 1 and 2 of the Selection System of Beneficiaries (SISBEN). They have been inquired about the perception they have of the functioning of the informal support offered not only by their relatives, but also by not family members. Besides, they were asked about the support they receive that comes from formal groups such as institutions and professionals in the field. It was evidenced through the development of this study that these social groups are affected due to older adults’ poor living conditions. However, the transfers and the reciprocal support help fulfill some of the needs this population group may have. It also undermines the false belief that elderly people play a passive role as a recipient of aid from formal social groups. Contrary to what was believed at the beginning of this study, it was evidenced the mutual help among the elderly despite the poor conditions, becoming in many cases a supplier of aid to other members of the social group.